Establishment of a serum IgG4 cut-off value for the differential diagnosis of IgG4-related disease in Chinese population. Issue 4 (3rd July 2016) - Li, Ping; Chen, Hua; Deng, Chuiwen; Wu, Ziyan; Lin, Wei; Zeng, Xiaofeng; Zhang, Wen; Zhang, Fengchun; Li, Yongzhe
Abstract: Objective : This study was performed to better know diagnosis associated with serum IgG4 concentration, and to explore the possibility for development of a serum IgG4 for IgG4-related disease (IgG4-RD) in Chinese populations. Methods : We studied retrospectively 497 IgG4 serum subclass measurements from Peking Union Medical College Hospital during the four-year period, including 242 IgG4-RD, 130 other diseases and 125 healthy individuals. Results : Serum IgG4 concentrations were significantly higher in IgG4-RD than in other pathologies (1662.9 ± 3760.9 mg/L, p < 0.001) and healthy individuals (538.2 ± 458.6 mg/L, p < 0.001). There were no significant differences in serum IgG4 level between other pathologies group and healthy individuals ( p = 0.075). Among the 242 IgG4-RD patients analyzed, serum IgG4 concentrations were normal in 46 patients (19.0%). We found 32 patients (24.6%) with elevated serum IgG4 levels among the 130 patients who suffered from other pathologies. There were seven (5.6%) with serum IgG4 over 1350 mg/L in healthy individuals. The ROC curve analysis revealed that the optimal sensitivity and specificity were 80.0% and 88.2%, respectively, at the concentration of 1575 mg/L for Chinese patients. Conclusions : Our study demonstrated that serum IgG4 elevation was not specific of IgG4-RD. Further studies are needed to define the sensibility and specificity of IgG4 values for the diagnosis of IgG4-RD.